PENGUATAN ‘INSTITUTIONAL BRANDING’ MUHAMMADIYAH KABUPATEN MALANG MELALUI PENGELOLAAN WEBSITE MAJELIS PELAYANAN SOSIAL - Fauzik Lendriyono; Demeiati Nur Kusumaningrum; Winda Hardyanti (Universitas Muhammadiyah Ponorogo, 2019)
The partner of the community service program is the Social Services Council (MPS) at the Muhammadiyah Regional Leadership in Malang Regency. The problem faced by MPS is the lack of updated information about MPS performance through the website of Muhammadiyah Regional Head (PDM). Based on the results of interviews with MPS administrators, this board division has not been able to carry out efforts to disseminate information using technological progress. There were lack of human resources to enhance the role and function of social service organizations in providing data and information. The optimalization of management of an organization's website is absolutely necessary as part of strengthening the image and spread of information. Thus, training on website management is a strategy to answer public needs as well as an effort to strengthen the organizational governance of MPS in Malang Regency. Technically, this training involved: 1) the IT administrator who responsible structurally in the board of management 2) the community service team of UMM as the speakers that internalized the subjects of organizational management, technical news writing and online media management. The results of the training on managing the MPS website have reached the target. MPS administrators has been able to collect and categorize data for online publication. This is indicated by 1) their ability to compile news texts based on the value of public interests and needs; 2) the ability to collect data and information previously obtained to be edited as website material; and 3) the ability to update the website appearance and link with the admin who manage the PDM website.